The oldest available name for the pampas cat of the Uruguayan Savannah ecoregion is Leopardus fasciatus (Larrañaga 1923) - Martínez-Lanfranco, Juan Andrés; González, Enrique M. (THERYA, 2022)
Based on a revision of historical and taxonomic accounts, we showed that Felis fasciatus Larrañaga, 1923, represents the oldest available Linnean name referable to the pampas cat endemic to the Uruguayan Savannah ecoregion, currently regarded as Leopardus munoai (Ximénez 1961). To anchor the name Felis fasciatus to Uruguayan specimens, we designated a neotype for this taxon with terra typica in Estancia San Cristóbal, Arroyo Limetas, Conchillas, Department of Colonia, Uruguay. Since Larrañaga's fasciatus represents a senior synonym of L. munoai, it takes precedence and, in compliance with the International Code of Zoological Nomenclature, it must therefore be used to refer to the "Uruguayan" pampas cat, L. fasciatus (Larrañaga 1923), for which we suggested the vernacular name "Larrañagaâ€™s pampas cat".